Analysis of Sand Casting Method in Manufacturing Ship Water Jet Propulsion Impeller Based on Software Simulation - Vicky Firmansyah; Jangka Rulianto; Eli Novitasari (WAVE: Jurnal Ilmiah Teknologi Maritim, 2026)
This research aims to analyze the casting process of an impeller used in a marine water jet propulsion system using the sand casting method, assisted by ProCAST simulation software. Two gating system designs were compared: one without a riser and one with a riser, along with three pouring temperature variations (630°C, 660°C, and 680°C) to identify casting defects. Simulation results show that the design with a riser produced a total shrinkage porosity of 6.67%. The solidification time for the design without a riser was recorded at 225 seconds, while the design with a riser reached 282 seconds. The Niyama criterion for the design without a riser ranged from 3.70 to 7.40 (k.sec)^0.5/cm, while the design with a riser increased to 4.96 to 9.93 (k.sec)^0.5/cm. Among the three pouring temperature variations, 660°C provided the most optimal results. The combination of riser design and 660°C pouring temperature yielded the best casting quality.